CCTV as a tool for early police intervention: Preliminary lessons from nine case studies. Issue 1 (January 2017) - Piza, Eric L; Caplan, Joel M; Kennedy, Leslie W
Abstract This study explores the prospect of utilizing CCTV as an early intervention mechanism to detect and disrupt street-level activity that can lead to violence. The analysis focuses on nine case studies in Newark, NJ, incorporating data from several sources, including video footage, computer-aided dispatch (CAD) system incident data, CAD event chronologies and face-to-face interviews with CCTV operators. The findings suggest that the benefits offered by CCTV, namely the instantaneous discovery and reporting of crime, may be rendered inconsequential by the process times associated with the differential-response policy of police dispatch. Potential methods by which police can more proactively utilize CCTV to prevent crime are discussed.